Distribution of two species of the Chamaeammygdalus section in the Rosaceae family from Eastern Kazakhstan (Experimental biology, 2020)
The article presents the information concerning to the distribution of two species – Amygdalus nana L. and Amygdalus ledebouriana Schlecht., the representatives of the Chamaeammygdalus section of the genus Amygdalus of the Rosaceae family in the Eastern Kazakhstan. As part of the study, about 100 herbarium sheets from various herbarium funds of various organizations were processed: Institute of Botany and Phytointroduction (Almaty), al-Farabi Kazakh National University (Almaty), Institute of Plant Biology and Biotechnology (Almaty), S. Amanzholova East Kazakhstan State University (Ust-Kamenogorsk), electronic database materials were also processed: The «Noah's Ark» Living Systems Depository, Lomonosov Moscow State University (Moscow), Plantarium, an atlas of species and an illustrated online identifier of plants (www.plantarium.ru) and the electronic search system Electronic Herbarium of S. Amanzholov East Kazakhstan State University (Ust-Kamenogorsk) and other sources. The studies were carried out by the route-reconnaissance method and the method of processing data on the distribution of floristic squares of floristic regions of the study area from 1932 to 2019. The article provides the tubs of the abstract of the Chamaeammygdalus section for the study area. The results are important for the description of the distribution area and conservation efforts for these two species.Key words: Amygdalus, Chamaeamygdalus, Amygdalus nana, Amygdalus ledebouriana, rare species, habitat.